PASSENGER CAR USAGE FOR COMMUTING TO WORK AS A FUNCTION OF LIMITED STAY AT CAR PARKS - Basarić, Valentina; Mitrović, Jelena; Papić, Zoran (Promet - Traffic&Transportation, 2013)
The analysis of the experiences in European cities, following the implementation of different transport policy measures, has led to a conclusion that parking policy measures have the dominant effect on the choice of private car as a mode of transport. This effect is the greatest for the commutes to work, characterized by the longest duration of parking space occupancy. Given the aforementioned experiences in developed European cities, the main aim of the study presented here was the determination of a relationship between limiting the duration of parking space occupancy in the Novi Sad city centre and the transport participants’ decision whether or not to use passenger car to commute to work. Based on the established interdependence between these parameters, we developed a mathematical model for calculating a number of expected car (commuting) journeys that terminate in the city centre as a function of limited duration of parking space occupancy.